Impact of pulmonary arterial systolic pressure on patients with mitral valve disease combined with atrial fibrillation - Zheng, Tie; Zhao, Yichen; Ye, Qing; Zheng, Shuai; Meng, Fei; Hu, Qiuming; Zhang, Haibo; Han, Jie; Tian, Baiyu; Zhu, Junming; Wang, Jiangang (Frontiers in Cardiovascular Medicine, 2023)
Objective To determine whether different changes of pulmonary artery systolic pressure (PASP) after surgeries have an impact on the long-term outcomes in patients with rheumatic and degenerative mitral valve (MV) disease and atrial fibrillation. Methods Between 2004 and 2016, 1,188 patients with rheumatic and degenerative MV disease undergoing MV and Cox-Maze procedure were identified. Clinic outcomes, as well as rhythm state and echocardiography indices in long-term follow-up were recorded. Patients were grouped by the changes of PASP (persistently normal, persistently increased, increased, and decreased) from preoperative estimation to follow-up. Results A complete echocardiography was performed at baseline and after 5 years. During follow-up, free of death and atrial fibrillation (AF) off antiarrhythmic drugs was 90 and 61%, 78 and 41% at 5 and 10 years, respectively. Survival rate was higher in patients with persistently normal and became worse in patients with persistently increased and increased PASP (log-rank 166.0, P < 0.0001). Moreover, the patients with persistently normal PASP had a lowest risk of recurrent AF (SHR: 0817; CI: 0.765–0.872; P < 0.0001) after considering death as a competing risk. A persistently normal PASP at follow-up and degenerative MV disease were associated with improved survival and sinus rhythm (SR) maintenance at multivariable Cox regression analysis (P < 0.05). Conclusion Patients with degenerative MV disease or have persistently normal PASP during follow-up have better survival and SR maintenance rate than patients with either rheumatic MV disease or persistently abnormal PASP.